Kinetics of anaerobic waste stabilization pond treatment - Sommai Chatsanguthai; Chongrak Polprasert; Orth, H.M.; Hanaki, K.; DANIDA (Bangkok : Asian Institute of Technology, 1986)
The highly organic wastewater was fed to anaerobic lab-scale ponds and the parameters analyzed were COD, TSS, TVS, Total sulfide, ph temperature and viscosity. Three different loadings were conducted over the period of investigation. The kinetic coefficients were determined by using different flow models. The results obtained indicated that the values of these coefficients increased with organic loading rate.
A research study submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1986
Keywords: Sewage lagoons; Sewage -- Purification -- Biological treatment